Management of Plant-Parasitic Nematodes in Florida Field Corn Production - Zane J. Grabau; Christopher Vann (EDIS, 2017)
This 8-page fact sheet written by Zane J. Grabau and Christopher Vann and published by the Department of Entomology and Nematology explains how corn producers can spot nematode symptoms, sample for nematodes, and manage nematode problems.http://edis.ifas.ufl.edu/ng014